SPEECH ACTS IN PUBLIC CONTROVERSY: A PRAGMATIC STUDY OF GUS EL’S CLARIFICATION ON VIRAL MISCONDUCT ACCUSATIONS - Muhammad Fahri Jaya Sudding; Fauzan Hari Sudding; Ashabul Kahfi Susanto; Ahmad Azhari; Andi Kamariah (Program Studi Pendidikan Bahasa Inggris, 2025)
Public clarification statements from religious figures play a significant role in shaping public perception during moral controversies, yet little is known about how such speakers use linguistic strategies to address accusations. This study examines how Gus El, an Indonesian religious leader, constructed his clarification in response to viral allegations of misconduct. Using a qualitative descriptive approach, the study analyzes a verbatim transcript of his YouTube clarification. The analysis focuses on the use of speech acts, politeness strategies, and selected apology elements. The findings show that expressive and commissive acts dominate the statement, particularly through explicit apologies, acknowledgement of personal fault, and commitments to self-improvement. Representative acts serve to contextualize and soften the perceived severity of the event. Politeness strategies, including humility, mitigation, and appeals to shared religious values, help the speaker manage face threats and maintain rapport with the audience. Overall, the clarification reflects a strategic use of language to express remorse, reduce negative judgment, and preserve credibility as a religious authority.